Master plans for pedestrian and bicycle transportation: community characteristics - Steinman, Lesley; Doescher, Mark; Levinger, David; Perry, Cynthia; Carter, Louise; Eyler, Amy; Aytur, Semra; Cradock, Angie L. I.; Evenson, Kelly R.; Heinrich, Katie M.; Kerr, Jacqueline; Litt, Jill; et al. (My University, 2012)
Background:Recent research demonstrates the importance of targeting the built environment to support individual physical activity, particularly for people experiencing health disparities. Master plans to promote biking and/or pedestrians (BPMPs) are a potential method for environmental change. This descriptive study aims to provide a snapshot of plan attributes and better understand demographic, social and transportation characteristics of communities with BPMPs. Methods: We collected a census sample of BPMPs from 4 states. Population and commuting data were obtained from national statistics. Results: 294 master plans were included, with most plans representing municipalities. 62% of plans targeted biking only, one-fifth targeted biking and walking, and 15% targeted walking only. The sampled locations have a similar demographic profile as the overall U.S. for median age and household income, people of color, high school education, and income inequality. The degree of racial diversity of sampled communities is slightly less than the U.S. average and the percentage of people who walk to work were slightly higher. Conclusions: Given that communities with master plans have a similar profile as the overall U.S., BPMPs could feasibly be spread to communities throughout the country. Further research is planned to describe BPMPs in detail toward informing future plan development.
Keywords: Physical activity; Policy; Public health